Spatial contextual cueing in handball players and action video game players - Schmidt, A. (Universität Magdeburg, 2019)
Team sport athletes and action video players have shown superior performance in visuospatial attentional processing in several tasks (Mann, Williams, Ward, & Janelle, 2007; Green & Bavelier, 2003). Masters (1992) suggest that implicit learning processes may allow expert performers fast and effortless performance, leading to more efficient decision-making and motor performance. However, investigation with athletes often focus on sport-specific situations (Abernethy, 1991) making it difficult to infer general underlying processes. A recent study, however, found improved context learning skills in athletes in a neutral, non-sport specific task with substantial visuospatial demands (Faubert, 2013). The three experiments presented in this thesis were designed to test if highlevel team sport athletes or action video game players have superior context learning skills. We investigated incidental context learning in visual search in order to examine the contribution of spatial context learning and search efficiency to the superior visuospatial performance of handball players and action video game players. To this end, we used a sport-specific pseudo 3-D contextual cueing task (search of the ball-carrying player in a playing field) and the original contextual cueing paradigm (search of a "T" among "L"-shapes; Chun & Jiang, 1998). We found comparable spatial contextual cueing of visual search in repeated displays in high-level amateur handball players, dedicated action video game players and normal controls. In contrast, both handball players and action video game players needed less time to analyze the contents of a search display than controls, measured as search time per display item, independent of display repetition, revealing superior attentive processing. Intercept data yield no evidence that non-search factors contribute to the contextual cueing effect for all groups. To conclude, our data do not indicate superior context learning skills in handball players or action video game players. Rather, both groups showed more efficient visual search in abstract displays that were not related to sport-specific situations